Real-world effectiveness of recombinant zoster vaccine in self-identified Chinese individuals aged ≥50 years in the United States - Ana Florea; Lina Sy; Lei Qian; Bradley Ackerson; Yi Luo; Jun Wu; Yanjun Cheng; Jennifer Ku; Leticia Vega Daily; Harpreet Takhar; Jeannie Song; Elizabeth Chmielewski-Yee; et al. (Taylor & Francis Group, 2024)
ABSTRACTWe evaluated the vaccine effectiveness (VE) of two doses of recombinant zoster vaccine (RZV) against herpes zoster (HZ) and postherpetic neuralgia (PHN) in Chinese adults at Kaiser Permanente Southern California (KPSC). Chinese KPSC members were identified based on self-reported ethnicity or self-reported preferred spoken/written language. Those aged ≥50 years who received two doses of RZV 4 weeks to ≤ 6 months apart were matched 1:4 to RZV unvaccinated Chinese members and followed through June 2022; second doses were accrued 6/1/2018-12/31/2020. We estimated incidence and adjusted hazard ratios (aHRs) with 95% confidence intervals (CIs) comparing outcomes (HZ and PHN). Adjusted VE (%) was calculated as (1−aHR)×100. 3978 RZV vaccinated Chinese members were matched to 15,912 RZV unvaccinated Chinese members. The incidence per 1000 person-years (95% CI) of HZ in the vaccinated group was 1.5 (0.9-2.5) and 10.9 (9.8-12.1) in the unvaccinated group; aHR (95% CI) was 0.12 (0.07-0.21). Adjusted VE (95% CI) was 87.6% (78.9-92.7) against HZ. We identified 0 PHN cases in the vaccinated group and 19 in the unvaccinated group. Among Chinese adults aged ≥50 years, two doses of RZV provided substantial protection against HZ and PHN supporting the real-world effectiveness of the vaccine in this population.